The Rise of Neoliberal Feminism. - Rottenberg, Catherine (Cultural Studies, 2014)
In this paper, I argue that we are currently witnessing the emergence of neoliberal feminism in the USA, which is most clearly articulated in two highly publicized and widely read ‘feminist manifestos’: Sheryl Sandberg's Lean In (a New York Times best-seller) and Anne-Marie Slaughter's ‘Why Women Still Can't Have It All’ (the most widely read piece in the history of the Atlantic). Concentrating on the shifting discursive registers in Lean In, I propose that the book can give us insight into the ways in which the husk of liberalism is being mobilized to spawn a neoliberal feminism as well as a new feminist subject. This feminist subject accepts full responsibility for her own well-being and self-care, which is increasingly predicated on crafting a felicitous work–family balance based on a cost-benefit calculus. I further pose the question of why neoliberalism has spawned a feminist rather than a female subject. Why, in other words, is there any need for the production of a neoliberal feminism, which draws attention to a specific kind of inequality and engenders a particularly feminist subject? While this new form of feminism can certainly be understood as yet another domain neoliberalism has colonized by producing its own variant, I suggest that it simultaneously serves a particular cultural purpose: it hollows out the potential of mainstream liberal feminism to underscore the constitutive contradictions of liberal democracy, and in this way further entrenches neoliberal rationality and an imperialist logic. Indeed, neoliberal feminism may be the latest discursive modality to (re)produce the USA as the bastion of progressive liberal democracy. Rather than deflecting internal criticism by shining the spotlight of oppressive practices onto other countries while overtly showcasing its enlightened superiority, this discursive formation actually generates its own internal critique of the USA. Yet, it simultaneously inscribes and circumscribes the permissible parameters of that very same critique.